A new look into credit procyclicality: International panel evidence - Ricardo Bebczuk; Tamara Burdisso; Jorge Carrera; Máximo Sangiácomo (Banco Central de la República Argentina (BCRA), Investigaciones Económicas (ie), 2011)
The goal of this paper is to provide up-to-date worldwide evidence on the short-term relationship between credit changes and output changes. Standard correlation methods, stateof-the-art panel Granger causality tests, and panel regressions were applied on a maximum sample of 144 countries over the period 1990-2007. Our results openly clash with two popular economic statements, namely, that credit is procyclical and that changes in credit have strong effects on private expenditure. According to the evidence produced, credit procyclicality -in the sense that the simple correlation coefficient is positive and significant at 10% or less- prevails in just 45% of the countries when annual data are used (23% with quarterly data). As for time precedence, our work suggests that, for the full sample, Granger causality runs from GDP to credit, while the often claimed causality from credit to GDP is a feature observable much less frequently - this behavior is observed only in financially developed countries. Results are robust to random resampling. Furthermore, after considering the potential presence of endogeneity, we contend that our results uncover not just mere Granger causality but economic causality. All in all, these findings have vast academic and policy implications.
Keywords: C33; E32; G10; 330; credit procyclicality; financial system; Granger causality; panel regressions; Kredit; Sozialprodukt; Kausalanalyse; Welt